Proceeding of International Heat Transfer Conference 9 1990
DOI: 10.1615/ihtc9.20
|View full text |Cite
|
Sign up to set email alerts
|

Flow Boiling in Vertical Down-Flow

Abstract: An experimental program has been conducted to investigate the onset of Ledinegg instability in vertical down-flow. For three size uniformly heated test sections with L/D ratios from 100 to 150, the pressure drop under subcooled boiling conditions has been obtained for a wide range of operating parameters. The results are presented in non-dimensional forms which correlate the important variables and provide techx_iques _or predicting the onset of flow instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The legends are indicated in Figure I and are identical for Figures I-9. It is shown that the model ofStaub (1_68) ( Figure 2) appears to be in good agreement with the data of Dougherty et al (1990), Whittle and Forgan (1967), Staub et al (1967), sad Ferrell (1964. These data reflect moderate and relatively high heat flux conditions.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The legends are indicated in Figure I and are identical for Figures I-9. It is shown that the model ofStaub (1_68) ( Figure 2) appears to be in good agreement with the data of Dougherty et al (1990), Whittle and Forgan (1967), Staub et al (1967), sad Ferrell (1964. These data reflect moderate and relatively high heat flux conditions.…”
supporting
confidence: 83%
“…where Y+ is the dimensionless distance from the wall to the top o/'th@bubble. Levy 1967 Dougherty, et al(1990) gives OFI data for vertical downwards flow in round tubes of six difl.erentdiameters. The OFI data were determined by a similar method as by Whittle and Forgan (1967).…”
mentioning
confidence: 99%
“…Lee and Bankoff [12] used calculations for symmetrical conditions between two flat plates to determine the empirical parameter Cs. By comparing their result with the hydraulic diameter concept with experimental data [7,21], obtained with circular tubes or rectangular channels, whose width and height were of similar magnitude.…”
Section: Limitationsmentioning
confidence: 92%
“…Experimental evidence [7,9,21] indicates that OFI for a flow with a pressuredriven boundary condition occurs very close to OSV. Hence, the prediction of OFI in the present model becomes the problem of predicting OSV.…”
Section: Basic Conceptmentioning
confidence: 97%
See 1 more Smart Citation